2022
DOI: 10.46747/cfp.680125
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care in acute care settings

Abstract: How can we best care for patients with acute illness in a hospital setting who also have dementia? Bottom lineFamily physicians play an important role in hospital care, particularly in smaller communities. Canada's hospitals are buckling under the rising numbers of patients with dementia, but many hospitals and health policy makers seem unaware. Acute illness and hospitalization are challenging for people with dementia, as hospitals are not well structured to optimally care for these patients, resulting in neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It is important for people with dementia to be invited and actively integrated into discussions of experiences and needs in new constructions. 21 When people with dementia participate in decisions and discussions about personal beliefs and values, society characterizes person-centered practices and culture. 4 , 12 , 16 In the aforementioned building cases, various interest organizations, such as Alzheimer’s Society, represented people with dementia, a diverse group that essentially has various requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important for people with dementia to be invited and actively integrated into discussions of experiences and needs in new constructions. 21 When people with dementia participate in decisions and discussions about personal beliefs and values, society characterizes person-centered practices and culture. 4 , 12 , 16 In the aforementioned building cases, various interest organizations, such as Alzheimer’s Society, represented people with dementia, a diverse group that essentially has various requirements.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous scholars have reported that evaluations from health personnel regarding the needs of people with dementia are not necessarily consistent with their actual needs and preferences. 20 , 21 Furthermore, it has been well documented that people with dementia can communicate their needs and lived experiences of having dementia. 21 , 22…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there has been an increasing call for the views of people with dementia to be included in research (Gove et al 2018; Scottish Dementia Working Group Research Sub-group, 2014). Research has been conducted which includes the perspectives of people with a diagnosis of AD (Beard, 2004; Caddell & Clare, 2011; Clare, 2002; Clare, 2003; Clare et al, 2006; Devlin et al, 2007; Dewitte et al, 2020; Frank & Forbes, 2017; Jensen et al, 2020; Pearce et al, 2002; Phinney & Chesla, 2003; Sabat & Harré, 1992). However, in comparison to research focussing upon the subjective experiences of people with AD, there is a paucity of research which incorporates the subjective experiences of people with FTD.…”
Section: Introductionmentioning
confidence: 99%